(untitled) (Studia austriaca, 2022)
This essay explores one of the films which dealt with the above-mentioned topics and had its cinematic release in the period under discussion – Kassbach, an adaptation of Helmut Zenker’s novel, which was made by Peter Patzak, a prominent Austrian director who passed away in 2021. In this respect, Kassbach would be a work that preceded numerous other Austrian films with a cinematic release in the 1980s and which, even before the Waldheim affair, would touch upon Austria’s difficult past. This article focuses on the film’s message that the lack of de-Nazification at the time, understood not only as a political and bureaucratic, but also as a psychological and social process, facilitates the establishment of right-wing radicalism.